2019
DOI: 10.1002/adma.201901033
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Optical Programming of Individual Meta‐Atoms Beyond the Effective Medium Approach

Abstract: Nanometer‐thick active metasurfaces (MSs) based on phase‐change materials (PCMs) enable compact photonic components, offering adjustable functionalities for the manipulation of light, such as polarization filtering, lensing, and beam steering. Commonly, they feature multiple operation states by switching the whole PCM fully between two states of drastically different optical properties. Intermediate states of the PCM are also exploited to obtain gradual resonance shifts, which are usually uniform over the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 47 publications
0
62
2
Order By: Relevance
“…However, for more accurate description of the crystallization profile during optical switching, multiphysics simulations should be taken into account. [ 48 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for more accurate description of the crystallization profile during optical switching, multiphysics simulations should be taken into account. [ 48 ]…”
Section: Methodsmentioning
confidence: 99%
“…Optical switching of the phase change material GST was realized by a custom‐made laser setup. [ 43,48 ] The light from a red, pulsed laser diode (λ = 660 nm) was focused through a 10× objective with a numerical aperture of 0.5 onto the sample surface. The sample was placed on a Thorlabs NanoMax‐TS (Max311/M) stage, which is movable in x , y , and z direction and connected to a Thorlabs closed‐loop piezo controller (BPC303).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Michel et al demonstrated that phase switching of the PCM with localized laser spots can arbitrarily tune the resonance of an individual hybrid metaatom up to one FWHM [167]. The investigated MS is composed of a 2D arrangement of Al nanorods deposited on a Si substrate and covered by a 75-nm-thick Ge 3 Sb 2 Te 6 layer which is protected by a thin capping film of ZnS-SiO 2 (see Figure 7A).…”
Section: Hybrid Plasmonic/pcm Metasurfaces For Local Amplitude Controlmentioning
confidence: 99%
“…[ 22–26 ] However, the tunability of PSOIs has been demonstrated with only “ON” and “OFF” states, although a couple of demonstrations of multilevel (even up to 11 states) and fully reversible tuning of metasurfaces have been reported. [ 27–31 ] Since the information can be coded in merely “ON” state, it is unavoidable to employ interleaved subarrays to achieve multiple functions with each one contributing to only a single function, resulting in the fundamental limitations of pixel loss, information infidelity, and low energy efficiency. [ 17 ] Additionally, interlacing different subarrays also increase the period of unit cells, resulting in a dramatic loss of light to spurious diffraction orders, which may further deteriorate the information fidelity and energy efficiency.…”
Section: Figurementioning
confidence: 99%